Rhodium(i)-catalyzed C-S bond formation via enantioselective carbenoid S-H insertion: catalytic asymmetric synthesis of α-thioesters - Sun, Yu-Tuo; Rao, Xiaofeng; Xu, Weici; Xu, Ming-Hua (ORGANIC CHEMISTRY FRONTIERS, 2022)
Asymmetric construction of C-S bonds through transition-metal catalysis is a challenging subject. By using chiral diene as the ligand, we have developed the first rhodium(i)-catalyzed asymmetric carbene insertion approach for C-S bond formation to access sulfur-substituted stereocenters under mild conditions, allowing the facile synthesis of a range of potentially valuable alpha-thioesters in high yields with moderate to good enantioselectivities.